A Theory of Divided Government - Alesina, Alberto; Rosenthal, Howard (Econometrica, 1996)
This paper extends the spatial theory of voting to the case in which policy choices depend upon the interaction between executive and the legislature. Voters are strategic and to analyze equilibrium the authors apply 'coalition proof' type refinements. The model has implications consistent with voting behavior in the United States: (1) split-ticket with some voters choosing one party for the presidency and the other for Congress; (2) for some parameter values, a divided government with different parties controlling the executive and the majority of the legislature; and (3) the mid-term electoral cycle with the party holding the presidency always losing votes in mid-term legislative elections.